Learner’ school violence using incident logbook: a qualitative research approach - Segalo, Letlhoyo; Hlatshwayo, Puleng (Technium Social Sciences Journal, 2021)
In this paper the notion of leaner’s school is revisited using a silent tool, incident logbook. Research shows that incidents of learner violence has escalated in South Africa unabated. Different approaches to describe and recommend strategies to alleviate cases of violence in schools have been undertaken. This paper aims to describe through incident logbook learner’s behaviour regarded as serious misconducts that involve violent acts. These violent acts might lead to expulsion or suspension of a learner from the school according to the South African Schools Act, 1996 and various school policies. Am interpretivist qualitative research was employed using a purposively sample of 5 incidents logbooks from five secondary schools. The researchers used a thematic data analysis using a Critical Peace Education (CPE) theory to discuss these incidents of school violence. The findings of the study show high incidents of recorded serious misconduct and violations of the school policies by learners by committing, violent acts such as physical, psychological, emotional abuses as well as thefts and vandalism of school and personal property. The research study recommends that CPE be used as tool to educate and foster peaceful co-existence in schools.